If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(4x + -6) = 27 Reorder the terms: -9(-6 + 4x) = 27 (-6 * -9 + 4x * -9) = 27 (54 + -36x) = 27 Solving 54 + -36x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + -36x = 27 + -54 Combine like terms: 54 + -54 = 0 0 + -36x = 27 + -54 -36x = 27 + -54 Combine like terms: 27 + -54 = -27 -36x = -27 Divide each side by '-36'. x = 0.75 Simplifying x = 0.75
| -4(4-3m)=-52 | | 16n^2-36= | | -17=5n-20 | | -(6x+(4x+3))=7-(5x+6) | | px-qr=-r | | 3(x-1)+8=-10 | | 2*3*4x-2*3*5x=6 | | 2=4c-2 | | 6n-20+5n=2(n+4)+4n-35 | | 6m=3m+36 | | 625=25g-105 | | -3=-2/3(x+2) | | (p^2-16)(p^2-3p-4)=0 | | 6m^2-18m-16= | | 9-4m=3 | | 155x=(120)(155)+120x | | 3x=7x+30 | | 5c-4-2c+1=10c+2 | | 145x=(120)(145)+120x | | 10-8z=2(5-4z) | | X+19=120 | | 7(x+7)-34= | | 150x=(125)(150)+125x | | 5t+8r=11 | | 145x=(125)(145)+125x | | 2x^2-9+1=0 | | 35-16t^2=6 | | -8x+2=3+10-30x | | 7+8(7+4)+9= | | 35-16t^2=35 | | -2.4x=-36 | | 35-16t^2=18 |